Assessment of Security Risks in Railway Transport using the Fuzzy Logical Deduction Method - Libor Hadacek; Lenka Sivakova; Radovan Sousek; Mikael Zeegers (Communications - Scientific letters of the University of Zilina, 2020)
The aim of the paper is to inform about the possibilities of using a fuzzy logical deduction in security practice. The fuzzy logic deduction allows to record the management experience in IF - THEN rules and does not require a precise description of the parameters of the controlled function. This property is an important asset for risk assessment in an incompletely defined environment. The application of the method is demonstrated in the security risk assessment of the physical protection of the national railway with a focus on the corridor railway lines and with regard to the future construction of high-speed railway lines in the Czech Republic. At present, it is a generally accepted fact that securing basic transport functions is a prerequisite for successful crisis management. These functions can be specified as road and rail negotiability.